Mekong hydropower: drivers of change and governance challenges - Grumbine, R. Edward; Dore, John; Jianchu Xu (Wiley, 2012)
The Mekong River is the longest watercourse in Southeast Asia. Although China has an extensive hydropower program underway on the Upper Mekong, as yet there are no dams on the river's lower mainstream. However, as many as 12 additional projects, which would generate substantial energy and wealth especially for Cambodia and Laos, are currently in the proposal stage for the Lower Mekong (LM). The cumulative effects of the LM hydropower projects – if built, and together with existing Chinese dams – will transform the Mekong by altering natural flow patterns and disrupting fisheries and other ecosystem services, to the detriment of the millions of people who depend on the river for their livelihoods. Proposals for new dam construction are driven by several factors, including changing human demographics and development needs, energy and food security concerns, economic cooperation, and climate change. We link these social, ecological, economic, and political forces to ongoing regional governance issues and discuss how to improve the quality of Mekong hydropower decision making in a complex, transboundary setting.